Large variability in the alkaloid content of Corydalis yanhusuo dietary supplements - Paula B. Luis; Claus Schneider (Frontiers in Pharmacology)
IntroductionExtracts from the rhizome of the traditional Chinese medicinal plant Corydalis yanhusuo (CY) mediate a number of biologic effects that are associated with its content of isoquinoline alkaloids. CY alkaloids have shown analgesic, cardioprotective, and anti-addictive effects in animal models of disease. Since CY alkaloids are available to consumers as dietary supplements we analyzed the content of alkaloids in 14 products including open powders, capsules, and liquid formulations, capturing a majority of the products available online in the US.MethodsNineteen alkaloids were quantified using HPLC analyses with diode array detection after extraction using a weak cation exchange column.ResultsTotal alkaloid content was highly variable among the products, ranging from below quantifiable in some to ≈11 mg/g in others. Five of the products had comparable content of alkaloids (9.5 ± 1.6 mg/g), equaling about the amount of alkaloids of an extract prepared from CY rhizome (12.7 mg/g). The other samples had much lower content (1.8 ± 0.9 mg/g), or alkaloids were below quantifiable. One of the products was highly enriched in tetrahydropalmatine (≈5 mg/g), suggesting adulteration from the natural product, and raising concerns about possible toxicologic liability.DiscussionConsidering alkaloid content as a key quality criterium for CY supplements, the large variability among the products seems unacceptable and makes it difficult for consumers to select products with an appropriate content of alkaloids.